Opening the electricity market to renewable energy: Making better use of the grid - Karsten Neuhoff (DIW Economic Bulletin, 2011)
Opening the electricity market to renewable energy sources would create flexibility for the further integration of renewable energy, leading to considerably lower costs and emissions. This requires the electricity markets to be reorganized in three ways. Firstly, most trading, and therefore production decision-making, is completed at least one day prior to electricity production. But it must be possible to make adjustments on shorter timescales, in order to effectively utilize wind forecasts, which are only relatively accurate a few hours ahead of production. Secondly, demand for operating reserve to stabilize the grid varies with the uncertainty of forecasts for wind and other generation. Most power plants can offer operating reserve, but only together with electricity. At present, however, operating reserve is traded separately from electricity, often in long-term contracts. And thirdly, network operators generally compensate market participants for grid constraints. But with around 200 GWs of new wind and solar capacity being built by 2020, grid expansion must be combined with transparent, market-based congestion management. The introduction of an independent system operator offering an integrated platform for short-term power trading using a pricing system that internalises network constraints (nodal pricing) could meet these conditions, allowing further openings of the power market for renewable electrical energy. Experience in the US and simulations for Europe show that international transmission capacity is up to 30% better utilized, congestion management alone yielding annual savings of 1 - 2 billion euros.
Keywords: L94; F14; L10; 330; market design; renewable energy; nodal pricing; transmission